PENERAPAN SISTEM AMONG DALAM PEMBENTUKAN KARAKTER SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMK TAMANSISWA YOGYAKARTA TAHUN PELAJARAN 2024/2025 - Mujiyono; Tarto (Program Magister Pendidikan IPS UPY, 2025)
This study aims to determine (1). How is the implementation of the among system in the formation of student character. (2). What are the supporting and inhibiting factors for the implementation of the Among System (3). How to overcome the obstacles faced by tutors in implementing the among system in the formation of student character. The research method used is descriptive qualitative with a phenomenological method, namely with data collection techniques through observation, interviews, and documentation. Data analysis uses data collection steps, data reduction, data presentation, and drawing conclusions. While checking the validity of the data is carried out by diligently observing the background of the implementation of the Among system learning, The results of the study show (1). The implementation of the among system in PKn learning is carried out with the stages of planning in PKn learning, integration in the curriculum, and planning in activities. The formation of student character through the educational trilogy, namely Ing Ngarso Sung Thuladha, Ing Madya Mangun Karsa and Tut Wuri Handayani, which is carried out through several activities, namely welcoming students, congregational Dhuhur prayer, posters of wise words and the behavior of tutors outside teaching hours. (2). Supporting factors include the existence of selected students from PPTS, BK tutors, school regulations that regulate student discipline. Inhibiting factors include the lack of teachers who have not all embraced the implementation of the among system, the character of students who come from broken homes, negative influences from friends and the school environment, and the paguron system has not been implemented. (3). Efforts to overcome obstacles are carried out by improving planning, implementation, and evaluation. character building strategy through implementing rules, habituating students, through liaison books, parent-teacher meetings, summons letters to parent-teacher, home visits, participating in extracurricular activities, collaborating with foundations and all school residents,